O PAPEL DO GESTOR ESCOLAR NO PROCESSO DE QUALIFICAÇÃO PROFISSIONAL DOS ALUNOS NO ENSINO MÉDIO UM ESTUDO DE CASO EM UMA ESCOLA PÚBLICA ESTADUAL PAULISTA - Oliveira, José Ricardo Duarte D (2014)
This work deals with the role of school management of secondary education, in vocational training to students in a public school process, as a new model of management education is discussed in recent years in Brazil. The Federal Government along with the Ministry of Education have submitted social program aimed at the young Brazilian to turn professional and be able to face a competitive job market. Among the program of the Government highlights the Prouni, (University for All Program) is a program of the Ministry of Education created in 2004 with the purpose of grant of partial and full education (50per cent of the tuition fee) in private institutions of higher learning in undergraduate courses exclusively designed to Brazilian students who have not attended higher education. These scholarships are awarded to students who participated in the National High School Exam (ESMS). In 2011, the Ministry of Education created the design of the National Program for Access to Technical Education and Employment (Pronatec) in order to expand the supply of vocational and technical education. With these and other programs offered by the government is intended to prepare young people for the labor market and other occupations that may be generating income. The guiding question of the study is: what is the role of the school manager of high school and their actions to the professional qualifications of the student? Through its objective, the research seeks to analyze the school management in secondary education, focusing on the role of manager of a public school, in vocational training to students of secondary education process. To assist in achieving this objective, two specific objectives were defined: a) analyze the actions and political conceptions of perception management by the faculty and staff of the school, b) analyze the actions aimed at the qualification for the vision of the students in the course and graduates. This is a survey that will be exploratory and descriptive qualitative. The desk research, interviews and semistructured, are part of the collection of data that will support the final analysis. The scientific and social contribution is discussed in this paper is a reflection on the school management of secondary education, the vocational qualification process of the students.